THE IMPLEMENTATION OF COLLABORATIVE WRITING TECHNIQUE IN TEACHING WRITING (RETAIN, 2020)
The purpose of this study is to describe the implementation of collaborative writing technique in writing text, especially in recount text. Writing is one the English skills that should be mastered by high school students. However, students thought that writing is not easy to do. They have some difficulties while doing writing. They do not know what they have to write while writing, and also they are confused in expressing their ideas into written form. Therefore, the researcher wants to describe the implementation of collaborative writing in teaching writing by the teacher. According to Fernández Dobao & Blum (2013), collaborative writing is a technique which students work together, share authorship, and share responsibility for all writing processes to produce final product. Students are expected to be helped in developing and gathering the ideas while writing a text by using collaborative writing technique. Moreover, this study uses qualitative approach. The subjects of this study are students of tenth graders in senior high school. The result of this study indicates that collaborative writing technique helps students to develop and gather ideas in writing a text. Collaborative writing technique also is an appropriate technique that can be used in teaching writing for high school students.